Composition and Structure in the Social Forestry Area Protected Forest Nagari Manganti Kecamatan Sumpur Kudus, Kabupaten Sijunjung - Marqfirokh, Ramadhana; Chairul, Chairul; Mukhtar, Erizal (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
The Social Forestry Area of the Nagari Manganti Protected Forest exhibits high vegetation diversity and the information on vegetation structure in this area remains limited. This study aims to analyze vegetation composition and structure across different growth stages, namely trees, saplings, and understory vegetation, as a scientific basis for sustainable forest management and conservation strategies. The research applied a purposive sampling method, with sample plots systematically established along transect lines. Data for tree and sapling strata were collected using non-destructive sampling methods, while understory vegetation and litter were obtained through destructive sampling. The results indicate that in the tree stratum, Rubiaceae was the dominant family, accounting for 14% of the total composition, consisting of two genera, two species, and six individuals, with Neonauclea sp. exhibiting the highest Important Value Index (IVI) at 26.84%. In the sapling stratum, Rubiaceae, Lauraceae, and Euphorbiaceae functioned as co-dominant families, contributing 18%, 13%, and 10% of the composition, respectively, with Litsea sp. recording the highest IVI at 22%. In the understory stratum, Rubiaceae was the most dominant family (36%), followed by Sapotaceae (11%) and Myrtaceae (10%), while Saraca sp. showed the highest IVI at 40.7%. Therefore, efforts to protect large-diameter trees need to be prioritized because they play an important role in carbon storage and ecosystem stability. They also maintain dominant species and are used in vegetation rehabilitation and enrichment activities, especially in landslide-prone areas and riverbanks.